Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3892/mmr.2018.9627
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin‑GPRC6A: An update of its clinical and biological multi‑organic interactions (Review)

Abstract: Osteocalcin is no longer regarded as a molecule exclusive to bone remodeling and osteogenesis, but as a hormone with manifold functions. The discovery of the interaction of osteocalcin with the G protein-coupled receptor family C group 6-member A (GPRC6A) receptor has accompanied the characterization of several roles that this peptide serves in body regulation and homeostasis. These roles include the modulation of memory in the brain, fertility in the testis, fat accumulation in the liver, incretins release in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 59 publications
(59 reference statements)
1
32
0
Order By: Relevance
“…This protein has also an effect in the control of bone mass, with positive effects on cortical mineral density. It is also demonstrated that irisin plays a crucial role in the reduction of sarcopenia in old people [55,56]. Osteocalcin is a bone-derived hormone-like protein.…”
Section: Discussionmentioning
confidence: 99%
“…This protein has also an effect in the control of bone mass, with positive effects on cortical mineral density. It is also demonstrated that irisin plays a crucial role in the reduction of sarcopenia in old people [55,56]. Osteocalcin is a bone-derived hormone-like protein.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mutations in the Phex gene are connected with rachitic changes in the bone growth plate, and this effect is mimicked by caspase inhibitors 36 . Osteocalcin is clinically important not only in bone regulation but also in many other tissues where it has a mediating role 37 . The regulation of Phex expression by caspase inhibition was described for the first time as was the specification of individual caspases in osteocalcin and Phex pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The main bone-derived mediator affecting the brain represents osteocalcin (OCN), which is encoded by the BGLAP gene and exclusively synthesized by osteoblasts. Undercarboxylated, bioactive OCN, initially considered as an inhibitor of bone mineralization [ 337 ], participates in systemic body regulation and homeostasis [ 338 ] primarily regulating insulin secretion, muscle adaptation as well as testosterone production in the testis [ 6 ]. In addition, OCN was recently discovered to transverse the BBB to enter the CNS, where it promotes spatial learning and memory while preventing anxiety-like behavior or even depression [ 6 ].…”
Section: Molecular Bases Of Brain-bone Crosstalkmentioning
confidence: 99%